Three-dimensional imaging using aberration-corrected scanning transmission and confocal electron microscopy - Cosgriff, E; D'Alfonso, A; Allen, L; Findlay, S; Kirkland, A; Nellist, P (2008)
A reduction in the focal depth of field as a result of the installation of aberration correctors in scanning transmission electron microscopy, allows three-dimensional information to be retrieved by optical depth sectioning. A three-dimensional representation of the specimen is achieved by recording a series of images over a range of focal values. Optical depth sectioning in zone-axis crystals is explored computationally using a Bloch wave analysis to explain the form of the electron intensity in the crystal as a function of depth. We find that the intensity maximum deviates from that of the expected defocus value due to pre-focusing by the atomic column and also due to channelling pendellosung. The possibility of performing bright-field imaging in a double corrected two lens system in a confocal arrangement is also investigated computationally. The method offers some advantages over depth sectioning using conventional transmission electron microscopy. © 2008 IOP Publishing Ltd.